The role of technology use, family support, and self-motivation in the business success of persons with disabilities amid the challenge of limited external support - Ibrahim, Fachmi; Lubis, Djuara P.; Muljono, Pudji; Sadono, Dwi (Edelweiss Applied Science and Technology, 2024)
The presence of individuals with disabilities in society often faces various challenges that hinder their full participation in entrepreneurial activities. Amid the rapid advancement of technology, opportunities to leverage information and communication technology (ICT) are becoming increasingly accessible. However, the challenges in running a business remain significant, particularly when support from the government and organizations is limited. This study aims to analyze the role of technology use, family support, and self-motivation in the business success of individuals with disabilities, despite the challenge of limited external support. This research employs a quantitative approach using SEM-PLS methodology to explore the relationships between relevant variables. The study was conducted on 43 businesses owned by individuals with disabilities across several regions in Indonesia, utilizing an online questionnaire as the data collection tool. The results indicate that technology use, family support, and self-motivation play significant roles in determining the success of businesses owned by individuals with disabilities. Technology use, particularly in marketing through social media, enables disabled entrepreneurs to overcome physical limitations and expand their market share. Family support, both emotional and financial, provides a crucial foundation for business success, especially when external support is limited. Self-motivation becomes an essential driving factor in facing various challenges, including limited access to external assistance, allowing individuals with disabilities to continue innovating and sustaining their businesses.